Image Encryption with Variable Length Key. Issue 3 (3rd May 2016) - Guanghui, Cao; Xing, Zhang; Yanjun, Liu
ABSTRACT: We propose a new image encryption algorithm with variable length running key based on a modified tent map. This modified tent map can generate uniform distribution pseudo-random number sequence. In the proposed image encryption, we employ the strategy of variable length running key which enlarges key value space, the strategy of one-time running key which is resilient to known/chosen plaintext attack, the strategy of cipher disturbance which minimizes dynamical degradation of digital chaos. Simulations have been carried out and the results demonstrate the strong survival ability of our scheme.